2018
DOI: 10.1051/e3sconf/20184500111
|View full text |Cite
|
Sign up to set email alerts
|

An assessment of the quality and use of rainwater as the basis for sustainable water management in suburban areas

Abstract: A common economic use of rainwater is the basis for strategies that will allow the water sector to adapt to progressive climate change. Rainwater is a basic part of water resources that ensures the renewal of the surface and groundwater, therefore they should be protected against pollution and be managed and used in places of rainfall. This is particularly true for heavily urbanized, agricultural and industrial areas. Stormwater collection and storage systems have been introduced in many countries [1]. The wat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 18 publications
2
12
0
Order By: Relevance
“…In addition, rainwater is usually considered to be of fairly good quality, especially for non-potable uses. However, their quality depends on many factors, including air quality, type of catchment management, type of roof coverage, and its decline [43][44][45][46]. In the case of using rainwater for non-potable uses (toilet flushing, garden watering), it is usually sufficient to use a filter to pre-treat them.…”
Section: Description Of the Simulation Modelmentioning
confidence: 99%
“…In addition, rainwater is usually considered to be of fairly good quality, especially for non-potable uses. However, their quality depends on many factors, including air quality, type of catchment management, type of roof coverage, and its decline [43][44][45][46]. In the case of using rainwater for non-potable uses (toilet flushing, garden watering), it is usually sufficient to use a filter to pre-treat them.…”
Section: Description Of the Simulation Modelmentioning
confidence: 99%
“…In addition, in contrast to rainwater, which rapidly runs off the substrate, dew has time to dissolve the aerosols falling on the condensing substrate for a whole night. values in the range 41-62 μS.cm −1 for dew in Poland; Zdeb et al [45] found ECs in the interval 40-150 μS.cm −1 in Poland on a non-industrialized suburban area. However, some of us have observed in Mirleft/Morocco and Gujarat/India, quite high ECs (respectively, 725 μS.cm −1 and 930 μS.cm −1 for dew) due to the high amount of aerosols in the vicinity of both sites [46,47].…”
Section: Electrical Conductivity (Ec)mentioning
confidence: 98%
“…When considering alternative water sources, special attention is paid to rainwater, which in most cases is characterized by a low degree of pollution which does not require advanced purification processes [18,19]. However, its quality depends on many factors, including air quality, the type of catchment management, the type of roof coverage and its decline [20][21][22]. Rainwater is an important alternative to tap water.…”
Section: Introductionmentioning
confidence: 99%